Antibiotic prophylaxis and clinical outcomes among older adults with recurrent urinary tract infection: cohort study. (28th August 2018) - Ahmed, Haroon; Farewell, Daniel; Jones, Hywel M; Francis, Nick A; Paranjothy, Shantini; Butler, Christopher C
Abstract: Background: clinical guidelines recommend antibiotic prophylaxis for preventing recurrent urinary tract infections (UTIs), but there is little evidence for their effectiveness in older adults. Methods: this was a retrospective cohort study of health records from 19, 696 adults aged ≥65 with recurrent UTIs. We used prescription records to ascertain ≥3 months' prophylaxis with trimethoprim, cefalexin or nitrofurantoin. We used random effects Cox recurrent event models to estimate hazard ratios (HR) and 95% confidence intervals (CI) for risks of clinical recurrence (primary outcome), acute antibiotic prescribing and hospitalisation. Results: of 4, 043 men and 15, 653 women aged ≥65 with recurrent UTIs, 508 men (12.6%) and 2, 229 women (14.2%) were prescribed antibiotic prophylaxis. In men, prophylaxis was associated with a reduced risk of clinical recurrence (HR, 0.49; 95% CI, 0.45–0.54), acute antibiotic prescribing (HR, 0.54; 95% CI, 0.51–0.57) and UTI-related hospitalisation (HR, 0.78; 95% CI, 0.64–0.94). In women, prophylaxis was also associated with a reduced risk of clinical recurrence (HR, 0.57; 95% CI, 0.55–0.59) and acute antibiotic prescribing (HR, 0.61; 95% CI, 0.59–0.62), but estimates of the risk of UTI-related hospitalisation were inconsistent between our main analysis (HR, 1.16; 95% CI, 1.05–1.28) and sensitivity analysis (HR, 0.82; 95% CI, 0.72–0.94). Conclusions: antibiotic prophylaxis was associated with lower rates of UTI recurrence and acute antibiotic prescribing in older adults. To fully understand the benefits and harms of prophylaxis, further research should determine the frequency of antibiotic-related adverse events and the impact on antimicrobial resistance and quality of life.